Active elements in the form of thin rods of square cross section for multichannel laser amplifiers. (August 2021) - Kuznetsov, I I
Abstract: We study thermally induced phase distortions of laser radiation in active elements in the form of thin rods of square cross section. The absence of aberrations and beam quality deterioration is demonstrated for these elements, due to which they can be used along with rods having a round cross section, differing from the latter by much higher technological efficiency of fabrication and mounting in the cooling system. A concept of compact and reliable multichannel solid-state amplifier based on such active elements is proposed, which allows one to use a multichannel fibre laser as a master system.